Comparative assessment of image quality for coronary CT angiography with iobitridol and two contrast agents with higher iodine concentrations: iopromide and iomeprol. A multicentre randomized double-blind trial - Achenbach, Stephan; Paul, Jean-Francois; Laurent, Francois; Becker, Hans-Christoph; Rengo, Marco; Caudron, Jerome; Leschka, Sebastian; Vignaux, Olivier; Knobloch, Gesine; Benea, Giorgio; Schlosser, Thomas; Andreu, Jordi; et al. (European Radiology, 2017)
OBJECTIVES: To demonstrate non-inferiority of iobitridol 350 for coronary CT angiography (CTA) compared to higher iodine content contrast media regarding rate of patients evaluable for the presence of coronary artery stenoses. METHODS: In this multicentre trial, 452 patients were randomized to receive iobitridol 350, iopromide 370 or iomeprol 400 and underwent coronary CTA using CT systems with 64-detector rows or more. Two core lab readers assessed 18 coronary segments per patient regarding image quality (score 0 = non diagnostic to 4 = excellent quality), vascular attenuation, signal and contrast to noise ratio (SNR, CNR). Patients were considered evaluable if no segment had a score of 0. RESULTS: Per-patient, the rate of fully evaluable CT scans was 92.1, 95.4 and 94.6 % for iobitridol, iopromide and iomeprol, respectively. Non-inferiority of iobitridol over the best comparator was demonstrated with a 95 % CI of the difference of [-8.8 to 2.1], with a pre-specified non-inferiority margin of -10 %. Although average attenuation increased with higher iodine concentrations, average SNR and CNR did not differ between groups. CONCLUSIONS: With current CT technology, iobitridol 350 mg iodine/ml is not inferior to contrast media with higher iodine concentrations in terms of image quality for coronary stenosis assessment. KEY POINTS: • Iodine concentration is an important parameter for image quality in coronary CTA. • Contrast enhancement must be balanced against the amount of iodine injected. • Iobitridol 350 is non-inferior compared to CM with higher iodine concentrations. • Higher attenuation with higher iodine concentrations, but no SNR or CNR differences.
EVALuna2:33652